Assessing small island prioritisation using species rarity: the tenebrionid beetles of Italy - Fattorini,Simone (2014)
We investigated conservation priorities of Italian small islands on the basis of tenebrionid species (Coleoptera Tenebrionidae) which are insects typically associated with coastal environments. Firstly, we estimated vulnerability of tenebrionid island communities in four different ways using their inter-island distribution, their overall rarity, their biogeographical characterization and the coastal perimeter of the occupied islands. Then, these four sets of vulnerability values were used to rank biotopes using the Biodiversity Conservation Concern index, BCC, which reflects the average rarity score of the species present in a site, and the Biodiversity Conservation Weight index, BCW, which reflects the sum of rarity scores of the same species assemblage. We found that most of the studied islands have been recovered as having some conservation value, but the Tuscan Islands, Ustica, Pantelleria and the Pelagie Islands were found to have highest priority.